Pengembangan Media Pembelajaran Talking Head Video Beranimasi - M Topit Hidayat; Rita Syofyan (Universitas Negeri Padang, 2023)
The goal of this research is to create learning media product that are valid and to use. This type of research is known as R&D. Using a 4-D development model with four stages: define, design, develop, and disseminate. The feasibility of expert validators who are knowledgeable in their fields was taken into consideration when testing this research on class XI IPS students at SMAN 3 Pariaman. These are the conclusions reached by the research: First, the material experts' validation scored 93.6% in the very feasible category. In the meantime, the media experts' validation received a score of 97.1%, placing it in the very feasible category. So, in general, based on the assessment of the media and material validators, it can be stated that it is very feasible to be used in learning economics on employment materials. Second, the teacher's assessment received a score of 97.5%, while the student's assessment received a score of 88.5%, placing them both in the very practical category. The study's findings lead us to the conclusion that the animated Talking Head Video as a teaching tool for economics subjects is valid and practical to use.